A chromosome-scale assembly of the major African malaria vector Anopheles funestus. Issue 6 (3rd June 2019) - Ghurye, Jay; Koren, Sergey; Small, Scott T; Redmond, Seth; Howell, Paul; Phillippy, Adam M; Besansky, Nora J
Abstract: Background: Anopheles funestus is one of the 3 most consequential and widespread vectors of human malaria in tropical Africa. However, the lack of a high-quality reference genome has hindered the association of phenotypic traits with their genetic basis in this important mosquito. Findings: Here we present a new high-quality A. funestus reference genome (AfunF3) assembled using 240× coverage of long-read single-molecule sequencing for contigging, combined with 100× coverage of short-read Hi-C data for chromosome scaffolding. The assembled contigs total 446 Mbp of sequence and contain substantial duplication due to alternative alleles present in the sequenced pool of mosquitos from the FUMOZ colony. Using alignment and depth-of-coverage information, these contigs were deduplicated to a 211 Mbp primary assembly, which is closer to the expected haploid genome size of 250 Mbp. This primary assembly consists of 1, 053 contigs organized into 3 chromosome-scale scaffolds with an N50 contig size of 632 kbp and an N50 scaffold size of 93.811 Mbp, representing a 100-fold improvement in continuity versus the current reference assembly, AfunF1. Conclusion: This highly contiguous and complete A. funestus reference genome assembly will serve as an improved basis for future studies of genomic variation and organization in this important disease vector.